2019
DOI: 10.1177/1933719118776790
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Progesterone Receptor Membrane Component 1 in Oxidative Stress—Induced Aging in Chorion Cells

Abstract: This study further demonstrated that oxidative stress-induced cell aging is one of the mechanisms of PPROM and PGRMC1 acts as a protective element for maintaining fetal membrane integrity by inhibiting oxidative stress-induced chorion cell aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 49 publications
5
24
0
Order By: Relevance
“…Our findings demonstrate that MPA but not P4 inhibit IL1β-induced MMP1 mRNA expression and IL8 mRNA levels and secreted protein levels through GR and not through PGRMC1 in amnion mesenchymal cells. These findings are similar to our previous work in amnion epithelial cells which demonstrated that the inhibition of cytokine-induced MMP9 activity and mRNA levels in amnion epithelial cells was mediated through GR ( Allen et al, 2019 ). Additionally, PGRMC1 localizes to the perinuclear area and the nucleus which is stark contrast to its expression pattern in amnion epithelial cells where it primarily localized to the cytoplasm and perinuclear area ( Allen et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings demonstrate that MPA but not P4 inhibit IL1β-induced MMP1 mRNA expression and IL8 mRNA levels and secreted protein levels through GR and not through PGRMC1 in amnion mesenchymal cells. These findings are similar to our previous work in amnion epithelial cells which demonstrated that the inhibition of cytokine-induced MMP9 activity and mRNA levels in amnion epithelial cells was mediated through GR ( Allen et al, 2019 ). Additionally, PGRMC1 localizes to the perinuclear area and the nucleus which is stark contrast to its expression pattern in amnion epithelial cells where it primarily localized to the cytoplasm and perinuclear area ( Allen et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…We have previously demonstrated that PGRMC1 protein expression is diminished in PPROM patients when compared with term and preterm no labor patients highlighting the fact that PGRMC1 may play a role in molecular mechanisms that lead to fetal membrane rupture ( Feng et al, 2014 ). Functionally we have shown that PGRMC1 partially mediates the inhibition of progestins on cytokine induced MMP9 activity in the HTR8 cytotrophoblast cell line and primary amnion epithelial cells ( Allen et al, 2014 , 2019 ). PGRMC1 may also play a role in oxidative stress induced senescence in fetal membranes ( Feng et al, 2019 ).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Two-dimensional (2D) single cell type culture experiments are most easy to run and low cost, and thus broadly utilized (Kendal-Wright, 2007;Menon et al, 2013;Meng et al, 2016;Sato et al, 2016;Feng et al, 2018b;Hadley et al, 2018;Jin et al, 2018). However, regardless of the cell origin (i.e., primary or immortalized) or cell layer (i.e., amnion or chorion), the major drawback is the limitations stemming from studying only a small part of the whole organ.…”
Section: In Vitro Cell Culture Techniquesmentioning
confidence: 99%
“…These effects are potentially mediated by nPRs functioning in the cytoplasm to directly affect other cell signaling pathways (66,67), by membrane-associated PRs (mPRs) that are coupled to specific intracellular signaling pathways (68)(69)(70)(71)(72)(73)(74), and/or by P4 (or its metabolites) interacting with neurotransmitter and peptide hormone receptors (75). Although the physiology role of putative mPRs as mediators of P4 actions is somewhat controversial (76)(77)(78), several studies suggest that certain forms mediate distinct pro-gestational actions of P4 in the myometrium, cervix and fetal membranes (79)(80)(81)(82)(83)(84)(85)(86).…”
Section: P4/pr Signaling In Human Pregnancy and Parturitionmentioning
confidence: 99%